Improvement of flexible rotor/active magnetic bearings system performance using pi-d control - Muminovic, Adis J. (Array, 2020)
Proportional–integral–derivative (PID) control is the most common control approach used to control active magnetic bearings system, especially in the case of supporting rigid rotors. In the case of flexible rotor support, the most common control is again PID control in combination with notch filters. Other control approaches, known as modern control theory, are still in development process and cannot be commonly found in real life industrial application. Right now, they are mostly used in research applications. In comparison to PID control, PI-D control implies that derivate element is in feedback loop instead in main branch of the system. In this paper, performances of flexible rotor/active magnetic bearing system were investigated in the case of PID and PI-D control, both in combination with notch filters. The performances of the system were analysed using an analysis in time domain by observing system response to step input and in frequency domain by observing a frequency response of sensitivity function.